Winter Eurasian cooling linked with the Atlantic Multidecadal Oscillation - Dehai Luo; Yanan Chen; Aiguo Dai; Mu Mu; Renhe Zhang; Simmonds Ian (Environmental Research Letters, 2017)
In this paper, we analyze observational and reanalysis data to demonstrate that the Atlantic Multidecadal Oscillation (AMO) significantly modulates winter Eurasian surface air temperature through its impact on the shape, frequency and persistence of Ural blocking (UB) events that last for 10–20 d. This impact results from changes in mid-high latitude westerly winds over Eurasia associated with the warming in the Barents–Kara Seas (BKS) through the AMO-driven high sea surface temperature and sea-ice decline and resultant weakening in meridional temperature gradients. The BKS warming has a strongest positive correlation with the AMO at a time lag of about 14 years. During the recent positive AMO phase, more persistent northwest–southeast (NW–SE) oriented UB events are favored by weakened westerly winds in Eurasian mid-high latitudes. Through cold atmospheric advection and radiative cooling, such UB events produce a strong, persistent and widespread cooling over Eurasia and enhance BKS warming during 1999–2015. However, the positive AMO phase cannot directly produce the Eurasian cooling if the UB is absent. Thus, we conclude that the recent AMO phase change is a major cause of the recent winter cooling over Eurasia through its impact on BKS temperature and sea ice, which in turn affect the meridional temperature gradient, the westerly winds and the UB events.